Ashy Dermatosis: A Narrative Literature Review - Oktafiani, Anindya; Muhammad Eko Irawanto (Open Access Indonesian Journal of Medical Reviews, 2023)
Ashy dermatosis (AD) or erythema dyschromicum perstans (EDP) is a type of hyperpigmented macules characterized by asymptomatic, gray macular lesions with a symmetrical distribution. Some of the predisposing factors for ashy dermatosis are intestinal parasitic infections, a bad environment such as consumption of ammonium nitrate, X-ray contrast media and genetic factors such as the HLA-DR4 allele. The clinical manifestations of ashy dermatosis are hyperpigmented or gray macules with slow progression and pigmentation abnormalities in the inner epidermal layer. The differential diagnosis of ashy dermatosis is with lichen planus pigmentosus, idiopathic eruptive macular pigmentation, and Riehl's melanosis. Diagnosis of ashy dermatosis needs to be linked between clinical findings and histopathological examination, other supporting examinations and differentiating it from other differential diagnoses. Management for patients with ashy dermatosis is with topical or systemic agents. For now, a combination of laser and tacrolimus ointment is recommended.